Single-fiber EMG in Migraine with or without Aura: Search for Correlations with Disability and Headache Intensity - Yetkin, Ozgun; Gumusyayla, Sadiye (Journal of Medical Science, 2024)
Background. The idea of a neuromuscular defect in migraine relates to the emergence of mutations in the CACNA1A gene that encodes the subunit of P/Q-type calcium channels in the motor nerve terminals. This study used single-fibre electromyography (SFEMG) to investigate the potential impact of an underlying channelopathy on subclinical neuromuscular transmission at the motor end plate in different types of migraine. Additionally, we sought to validate previous findings, explore the pathophysiology, and examine any potential relationship between neuromuscular dysfunction and disease severity using the Migraine Disability Assessment Scale (MIDAS) and Visual Analog Scale (VAS).Material and methods. We enrolled 25 healthy volunteers, 30 migraineurs with aura and 30 without aura diagnosed according to the 2018 criteria of the International Headache Society. Voluntary SFEMG was performed on the frontalis muscle. Jitter values were analysed, including the mean individual jitter values of the migraine group, the number of fibers with increased jitter, the mean Mean Consecutive Difference (MCD), and the lowest and highest jitter values, which were then compared with those of the control group. The intensity of the migraine attacks was assessed using the VAS, while disability was evaluated using the MIDAS.Results. Our findings revealed that the highest jitter values in migraine patients were significantly higher than those observed in the control group. Furthermore, we conducted a subgroup analysis within the migraine group and found that individuals with aura had higher average MCD values compared to those without aura and the control group. Additionally, we examined the association between MIDAS and VAS scores with increased jitter values and neuromuscular transmission abnormalities, but no statistically significant correlation was found (p=0.327).Conclusions. Our study supports the presence of motor endplate dysfunction in migraines, as indicated by previous literature, particularly in migraines with aura when compared to individuals without aura and controls. This finding aligns with the concept that this dysfunction may stem from a channelopathy associated with a genetic predisposition. Additionally, we found no clinical relationship between the neuromuscular disorder, the severity of the disease, and its disability.
Keywords: jitter; migraine; neuromuscular transmission; single-fiber electromyography